Comparison of the susceptibility and resistance of four marine perciform fishes to Cryptocaryon irritans infection. Issue 77 (June 2018) - Yin, Fei; Liu, Wenchao; Bao, Peibo; Jin, Shan; Qian, Dong; Wang, Jiteng; Tang, Baojun
Abstract: Cryptocaryon irritans is a type of marine ectoparasitic ciliate that infects teleost fishes. To illustrate the susceptibility and innate immune mechanism of fishes to C. irritans, four species of marine perciform fishes were selected in Fujian Province, a high-prevalencearea of cryptocaryoniasis in China. The survival, diameter/number of tomonts, and infection ratio among Larimichthys crocea, Lateolabrax japonicus, Pagrus major, and Nibea albiflora were compared after artificial infection. Meanwhile, the immobilization titers of four fish species with no C. irritans infection were detected. Results showed that survival and serum immobilization titer of N. albiflora were significantly higher than those of the other three fish species. A strong negative linear correlation was found between the survival/serum immobilization titer and the mean tomont diameter. In addition, the smallest C. irritans infection ratio was found in N. albiflora, implying that the serum of fishes especially that of N. albiflora, inhibited the development of parasitic C. irritans cells, and the smallest tomont size was directly related to the number of infective theronts corresponding to the highest survival of fish. Moreover, complement activity inhibition assays suggested that the alternative complement pathway might play a major role in C. irritans resistance. Highlights: Susceptibility and resistance of four marine perciform fishes to C. irritans infection. N. albiflora has the strongest anti- C. irritans resistance among four fish species. Alternative complement pathway of N. albiflora might play a major role in C. irritans resistance.